Hierarchies from D-brane instantons in globally defined Calabi-Yau orientifolds - Cvetič, Mirjam; Weigand, Timo (Physical review letters, 2008)
We construct the first globally consistent semirealistic type I string vacua on an elliptically fibered manifold where the zero modes of the Euclidean D1-instanton sector allow for the generation of nonperturbative Majorana masses of an intermediate scale. In another class of global models, a D1-brane instanton can generate a Polonyi-type superpotential breaking supersymmetry at an exponentially suppressed scale.